Nowe kino rosyjskie w Polsce: przypadek Aleksieja Bałabanowa - Szymczak, Grzegorz (Przegląd Rusycystyczny, 2012)
Grzegorz Szymczak Uniwersytet Warszawski, Warszawa, Poland g.szymczak@uw.edu.pl НОВОЕ РОССИЙСКОЕ КИНО В ПОЛЬШЕ: СЛУЧАЙ АЛЕКСЕЯ БАЛАБАНОВА Резюме В статье затронута тема рецепции современной российской кинематографии в Поль-ше после 1989 года на примере творчества Алексея Балабанова. Девяностые годы характеризовались резким ограничением доступа к российской культуре в Польше, но в начале XXI века, особенно в последние пять лет, ситуация меняется в лучшую сторону, доказательством чего является, например, популярность фестиваля российских фильмов „Спутник над Польшей”. Растущий интерес как польских критиков, так и зрителей к фильмам Алексея Балабанова может послужить экземплификацией этой тенденции. THE NEW RUSSIAN CINEMA IN POLAND: THE CASE OF ALEXEI BALABANOV Summary The article deals with reception of contemporary Russian cinematography in Poland after 1989 on the example of Alexei Balabanov films. The nineties was the period of limited access to Russian culture in Poland, but at the beginning of XXI century — especially last five years — situation is much better, and it could be confirmed, for instance, by the popularity of Russian film festival “Sputnik over Poland”. The rising interest of Polish critics and viewers to films by Alexei Balabanov is exemplification of this tendency.